A study oh reasons and financial effects on a sample of companies / Mazian Hassan - Hassan, Mazian (Faculty of Accountancy, 1992)
Acquisition is the purchase of the shares or undertaking of a company in exchange for cash, shares or other securities of the acquiring company, or partly for cash and shares or other securities. Acquisition is made with reasons or objectives which are expected to be achieved by the acquiring company. These objectives will bring financial effects to the acquiring company, Financial ratios can be used as tools for measuring and analysing the financial effects of the acquisition by comparing the acquiring company's pre and post acquisition financial ratios. The degree of success of the quantitative reasons or objectives—of the acquiring company upon the acquisition can be measured by relating the reasons and the results of the financial ratios.